Capacity building and disaster resilient village simulation (gamtana) in the environmental village of Universitas Malikussaleh [Peningkatan kapasitas dan simulasi gampong tangguh bencana (gamtana) di gampong lingkungan Universitas Malikussaleh] - Sayuti, Muhammad; Daud, Muhammad; Hasibuan, Arnawan; Mariyudi, M; Verawaty Siregar, Widyana; Puspasari, Cindenia; Irfansyah, Dedi; Qurratu Aini, Nyak; Kurniawan, Dicky; Almunadiansyah, Rizky; Roid, Fahrian (Buletin Pengabdian, 2025)
This community engagement initiative focuses on improving disaster resilience in seven villages (gampong) around Universitas Malikussaleh through capacity building and simulated disaster response exercises, contributing to the establishment of Gampong Tangguh Bencana (GAMTANA), or Disaster Resilient Villages. This community empowerment program aims to foster self-reliance in disaster preparedness and response within the community, operating under a voluntary task force model. After initial coordination with village leaders (Keuchik), a training and simulation program was implemented, in accordance with roles and responsibilities that have been defined in GAMTANA's organizational structure. The results demonstrated the effectiveness of this program as demonstrated by the active participation and successful execution of assigned tasks by all participants, reflecting their understanding of their respective functions within the disaster response framework. In conclusion, this initiative successfully equipped community members with the necessary skills and knowledge to carry out their roles within the GAMTANA task force, thereby strengthening local disaster resilience and promoting community-based disaster management.